Education and skill mismatches in the German labour market : the role of vocational and occupational specificity from a career perspective - Bischof, Stephan [Verfasser] (My University, 2026)
“Previous research shows that individuals’ educational level is associated with skill mismatch, but knowledge about the influence of horizontal dimensions of education and education’s variation throughout the career is limited. This study analyses the link between education and skill mismatch by considering the influence of educational levels, vocational specificity, and occupational specificity from a career perspective. Using the survey wave 2016 of the German NEPS Adult Cohort, I find that individuals with a higher educational level are less likely to be underskilled, but more likely to be overskilled. Conversely, higher vocational specificity is associated with a higher likelihood of underskilling but a lower likelihood of overskilling, whereas occupational specificity is not significantly related to skill mismatches. The findings also highlight that the link between education and skill mismatch varies with time since graduation, and that the role of vocational and occupational specificity differs across educational levels.” (author‘s abstract; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; 370; Bildungsniveau; Qualifikationsniveau; Spezialisierung; Einflussfaktor; Überqualifikation; Unterqualifikation; Qualifikationsforschung; Nationales Bildungspanel